The Influence of Information Technology, Individual Performance, and Sales Volume on Increasing Profits in SMEs in Cilegon - Erlina Sari Pohan; Udi Iswadi (LPPM Universitas Terbuka, 2021)
This study aims to determine the increase in profits as seen from the information technology variables, individual performance and sales volume at the SMEs Cilegon City. The location of this research is determined by the purposive method, namely SMEs registered at the Cilegon City Cooperative Office. The research method was carried out quantitatively by using multiple regression methods. The sampling method used was purposive sampling, the sample used was 23 samples from a total of 29 populations. Data collection techniques are primary using questionnaires and interviews, secondary is BPS, Cilegon City Cooperative Office, books and journals. While the data analysis used first is the classical assumption test and then hypothesis testing is carried out. The results showed that information technology variables and sales volume variables had an effect on increasing SME profits in Cilegon City. Meanwhile, individual performance has no effect on increasing profits at SMEs in Cilegon City.